Tomb raiders : real tales of grave robberies - Cummings, Judy Dodge (Mystery & mayhem., 2018)
Examines a series of true stories involving grave robbing and those who robbed them, body snatchers, crooks of the crypt, from Jamestown Virginia to Sipán, Peru.